Correction of critical hypernatremia in severe burn trauma - I. Yu. Samatov; A. L. Weinberg; E. I. Streltsova; E. I. Vereshchagin (Сибирский научный медицинский журнал, 2020)
Hypernatremia along with septic complications is the most frequent and dangerous complication in patients with severe burn trauma. The intravenous infusion of hypoosmolar solutions is considered to be a common tactic in overcoming critical hypernatremia, although the safety and effectiveness of this approach is questioned. The aim of the work was to clarify the pathogenesis of hypernatremia and define the tactic for its correction in the acute period of severe burn trauma. Material and Methods. The retrospective study included 82 adult patients treated in the ICU of the Burn Trauma Center of Novosibirsk Regional Clinical Hospital between 2015–2018 years. There were patients both with partial thickness burns TBSA >40 % or with full thickness burns TBSA 20 % with or without the thermoinhalation trauma. Results. Hypernatremia (serum Na > 150 mmol/L) usually occurred 4–6 days after a severe burn injury. This complication was detected in 27 % of patients. Cortisol serum levels were at the upper limit of the norm, meantime the serum concentration of aldosterone was significantly increased on 3rd day after trauma. Based on the obtained data, hypernatremia was corrected using enteral rehydration (oral water up to 20–30 ml/kg/day), Spironolactone (200–300 mg/day), intravenous titration of furosemide in small doses (60–100 mg/day). Permanent renal replacement therapy started when a patient›s serum sodium level was greater than 160–163 mmol/L. Conclusion. Significant increase of the serum aldosterone concentration in patients with severe burn trauma was noted by the 3 day, so the use of spironolactone should begin in these terms. Titrated intravenous introduction of furosemide in small doses (60–100 mg/day) allows removing sodium without adverse effects. In addition, the use of additional enteral rehydration is necessary.